Media and mass campaign on CSA/CIS and One-health concept and innovations - Attuquaye, Victor; Agyeman, Duah Solomon; Oppong-Mensah, Birgitta; Gaitu, Christopher; Nikoi, Gordon; Yeboah, Stephen; Adomako, Joseph; Martey, Francisca; Kyere, Reginald; Osae, Michael (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
AICCRA Ghana is leverage the wide network of media and mass dissemination tools to scale Climate Smart Innovations and Climate Information Services to farmers